Analysis of inrush current impacts towards transformer protection capability / Norhuda Hamzah - Norhuda, Hamzah (2017)
Inrush current in power transformer is also known as magnetizing inrush current, which the transformer windings are linked magnetically by flux in the transformer core. Magnetizing inrush current in transformer is the current which is drawn by a transformer when transformer is being energized. The inrush current has a large DC-component and rich of harmonics where the fundamental frequency and the second harmonic are dominating. Magnetizing inrush current is not a fault current, and therefore during inrush current event, transformer protection must remain stable. Differential protection is the most widely used methods for protecting power transformer against internal fault. The differential transformer protection can identify the inrush current by detecting the second harmonic content that used in this research. In this project, transformer differential protection has been modeled in PSCAD software. There are four main components in PSCAD library used for modeling of the relay, which are Fast Fourier Transform (FFT), Dual Slope Current Differential Relay, Overcurrent Detection Block, and relay logic components for tripping signal. The FFT component used for extracting the fundamental and second harmonic current, and the Dual Slope Current Differential Relay component for differential current and bias current setting. The OC Detection Block component functions as inrush current blocking. The tripping signal in transformer differential relay used to show the operation of the relay. The analysis has been simulated based on two case studies with different capacities and voltage level of transformers.